1992
DOI: 10.1063/1.106446
|View full text |Cite
|
Sign up to set email alerts
|

Method for the local incorporation of Er into LiNbO3 guided wave optic devices by Ti co-diffusion

Abstract: Co-diffusion of Er with Ti into LiNbOs produces more than an order of magnitude enhancement in Er diffusivity over that achieved by ion implanting and thermal diffusion. The enhancement is dependent on the amount of Ti present. Er doped channel waveguide fabrication is completely compatible with standard Ti:LiNbOs technology. Fluorescence measurements from co-diffused and bulk grown Er doped LiNbOs show that the co-diffused Er3 + is in the LiNbO, phase.LiNbOs guided wave optics has produced the most sophistica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

1994
1994
2010
2010

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(13 citation statements)
references
References 6 publications
1
12
0
Order By: Relevance
“…4 The 4113/2 lifetime has been measured in one study [4] to be 7200 gs, and 7000 gs has been reported in another work [6]. These values are in agreement with our calculated radiative lifetime of 6450 gs within an uncurtainty of 10% which is typical for the Judd-Ofelt method.…”
Section: )6supporting
confidence: 90%
See 2 more Smart Citations
“…4 The 4113/2 lifetime has been measured in one study [4] to be 7200 gs, and 7000 gs has been reported in another work [6]. These values are in agreement with our calculated radiative lifetime of 6450 gs within an uncurtainty of 10% which is typical for the Judd-Ofelt method.…”
Section: )6supporting
confidence: 90%
“…In the limit of weak excitation an ion in an excited state decays with a measured lifetime zm given by: l/rm = Ar+Aph+Atr, (6) where Ar is the radiative transition rate, Aph is the nonradiative transition rate due to multiphonon emission and Atr is the rate of nonradiative energy transfer. When the concentration of active ions is sufficiently low, the last term in (6) becomes small and the decay is governed by radiative transitions and multiphonon relaxation.…”
Section: Multiphonon Relaxationmentioning
confidence: 99%
See 1 more Smart Citation
“…Although, optical net gain has been demonstrated by the diffusion of Er in LiNbO 3 at a temperature of 1100°C for 100 hours [3], selective diffusion is difficult to complete because of the lack of visibility in photolithographic mask alignments. In contrast, the Er and Ti co-diffusion process not only enhances the diffusivity of Er in LiNbO 3 [4], thus leading to shorter diffusion times, but also improves the visibility for the mask alignments. Therefore, the aim of this work was the demonstration of the fabrication of optical waveguide amplifiers in X-cut Y-propagating LiNbO 3 by Er and Ti co-diffusion.…”
Section: Introductionmentioning
confidence: 84%
“…After this period, basic research on optical spectroscopy of rare-earth ions in perovskite-type oxides was faded out except some, namely LiNbO 3 crystals [8,9]. Attention from a practical point of view was not paid either to most of these materials, because observed luminescence efficiency was low.…”
Section: Introductionmentioning
confidence: 96%